2011
DOI: 10.1016/j.neuron.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of Direction Selectivity in Mouse Cortical Neurons

Abstract: Previous studies of the ferret visual cortex indicate that the development of direction selectivity requires visual experience. Here, we used two-photon calcium imaging to study the development of direction selectivity in layer 2/3 neurons of the mouse visual cortex in vivo. Surprisingly, just after eye opening nearly all orientation-selective neurons were also direction selective. During later development, the number of neurons responding to drifting gratings increased in parallel with the fraction of neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
153
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(181 citation statements)
references
References 47 publications
25
153
2
1
Order By: Relevance
“…A second difference with the previous MEA study is that alignment of the preferred directions along the temporal and ventral quadrants were overrepresented [5,32], a bias that persisted in recordings from V1 at eye-opening [33] but was not seen here ( Figure 2; Figure S3). Interestingly, it was recently shown that DSGC preferred directions vary retinotopically (Sabbah, S., Gemmer, J., Castro, G., Siegel, J.…”
Section: Distribution Of Dsgc Preferred Directions Along the Cardinalcontrasting
confidence: 82%
“…A second difference with the previous MEA study is that alignment of the preferred directions along the temporal and ventral quadrants were overrepresented [5,32], a bias that persisted in recordings from V1 at eye-opening [33] but was not seen here ( Figure 2; Figure S3). Interestingly, it was recently shown that DSGC preferred directions vary retinotopically (Sabbah, S., Gemmer, J., Castro, G., Siegel, J.…”
Section: Distribution Of Dsgc Preferred Directions Along the Cardinalcontrasting
confidence: 82%
“…No maps for stimulus orientation, direction, ocular dominance, or binocular disparity have been reported in the visual cortex of adult wild-type rodents 6,[19][20][21] . However, the ease of loading neurons with fluorescent dyes and attaining imaging stability, together with the powerful genetic tools available for mice has resulted in the vast majority of studies using two-photon imaging of the cerebral cortex being performed in rodents instead of ferrets, cats, and monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Pattern-motion-selective cells in mouse area V1 could similarly obtain their properties from local V1 component-selective and unclassified directionselective units. Alternatively, they could inherit their direction selectivity from subcortical targets, such as the pathway described by Cruz-Martin et al (2014) originating in direction-selective retinal ganglion cells (Cruz-Martin et al, 2014) and supplying the direction information into the top layers of V1 through the orientation-and direction-selective units found in a mouse LGN shell (Piscopo et al, 2013;Marshel et al, 2011), bypassing layer 4. If the PM-selective cells in mouse V1 inherited their properties from local V1 direction-selective neurons, or LGN directionselective neurons via a process analogous to the monkey MT pooling of V1 inputs as described in cascade models (Rust et al, 2006), one would expect them to show broader direction-tuning bandwidth for gratings compared with component and unclassified cells in V1, strong opponent motion inhibition, and crossangle invariance of PM-selectivity (Rust et al, 2006;Solomon et al, 2011).…”
Section: Origins Of Pattern-motion Selectivity In Mouse V1mentioning
confidence: 99%